2016
DOI: 10.1148/radiol.2015150641
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Clinical Value of CT-guided125I Brachytherapy for Bilateral Lung Recurrences from Colorectal Carcinoma

Abstract: CT-guided (125)I brachytherapy is feasible and safe for the treatment of bilateral lung recurrences from colorectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Many studies have indicated that MWA is an effective, feasible, and minimally invasive treatment for early stage of NSCLC . Brachytherapy has demonstrated good local control for salvage therapy of recurrent lung malignancies after failure of chemotherapy or radiotherapy . Theoretically, both procedures are capable of destroying small recurrences of NSCLC with a diameter <4 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have indicated that MWA is an effective, feasible, and minimally invasive treatment for early stage of NSCLC . Brachytherapy has demonstrated good local control for salvage therapy of recurrent lung malignancies after failure of chemotherapy or radiotherapy . Theoretically, both procedures are capable of destroying small recurrences of NSCLC with a diameter <4 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with RFA, MWA demonstrated faster ablation times, larger ablation zones, and higher intratumoral temperatures in ex and in vivo animal models, as well as human patients, which brings broad indications. Iodine‐125 seed brachytherapy has been demonstrated to be a feasible and effective treatment for lung tumors, with a good local control rate and improved disease‐free survival (DFS) . To the best of our knowledge, there has been no research which has compared MWA and iodine‐125 seed brachytherapy as a salvage treatment for local recurrence of NSCLC after failure of first‐line chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Understandably, the therapeutic efficacy of surgical treatment combined with external radiotherapy and/or chemotherapy is inadequate and unsatisfactory. Three-dimensional stereotactic radiotherapy using interstitial implantation of 125 I seeds is now considered a novel complement to surgery and external radiotherapy [2, 3, 4]. …”
Section: Purposementioning
confidence: 99%
“…Many studies have evaluated 125 I brachytherapy have a good curative effect in pancreatic cancer, liver cancer, lung cancer, prostate cancer, and gynecological and brain malignancies [14]. The 125 I seed is a miniature radioactive source; it continuously delivers low doses of x-rays and γ-rays, and the radiation dose decreases rapidly with increasing distance from the source [15].…”
Section: Introductionmentioning
confidence: 99%